Effects of Wage Differentials, MFA, and GSP on Exports in the Bangladesh Textile and Garment Industry - Bhuyan, Md Iqbal; Oh, Keunyeob (International economic journal, 2024)
In this paper, we investigate the effect of inter-country wage differentials on textile and garment (T&G) exports of Bangladesh and present an account of the important issue of why textile and garment exports are directed from developing countries to developed countries. Our empirical results imply that the wage differentials between developed and developing countries constitute one of the main drivers of T&G exports. In addition, we checked other factors such as the Multi-Fiber Arrangement (MFA) and the Generalized System of Preferences (GSP) by including dummy variables representing the MFA quota withdrawal and the GSP. We found that removal of the MFA had a significant negative effect, as expected. Our study confirms the positive correlation between GSP and exports. After phasing out the MFA and its quota system, the wage differentials not only boost the T&G exports from Bangladesh, but also increase the effectiveness of GSP. Given such findings, we discuss relevant policy implications.